Health policy and European Union enlargement - McKee, Martin; MacLehose, Laura; Nolte, Ellen (Open University Press, 2004)
The process of European Union enlargement will have major implications for health and health care policy throughout Europe. The diversity of countries involved in this process and the challenges they face is the focus of this book. This book will be of interest to students of health policy, economics, public policy and management, as well as health managers and policy makers.
European Observatory on Health Systems and Policies series
Keywords: Public Health; Health Policy; veřejné zdravotnictví; zdravotní politika; management, organizace a řízení zdravotnictví; Evropská unie; Health Care Economics and Organizations; politologie, politika, zdravotní politika; ekonomika a organizace zdravotní péče; European Union